Biomass‐Inspired Solar Evaporator for Simultaneous Steam and Power Generation Enhanced by Thermal‐Electric Effect. Issue 12 (3rd November 2022) - Liu, Gang; Yu, Fang; Irshad, Muhammad Sultan; Xiong, Xin; Guo, Zhenzhen; Wang, Junshi; Xiao, Bo; Lin, Liangyou; Wang, Xianbao
Abstract : Solar‐driven interfacial evaporation systems have been considered to achieve broad application prospects in the field of cogeneration of steam and electricity. However, the electricity generated is often independent of the photothermal system, hindering their integration. Compared with traditional materials such as metals and semiconductors, the application of biomass materials can solve the problems of high cost and environmental pollution in the expansion and relevance of interfacial evaporation technology. Herein, the solar evaporator composed of carbonized sphagnum palustre with cellulose fabric (CSPF) is fabricated for simultaneous steam production and power generation. Additionally, a device consisting of the CSPF and other accessories such as heating wires is designed to enhance steam production by self‐driven electrothermal heating. The self‐driven solar evaporator endows enhanced evaporation rates to 2.12 kg m −2 h −1 under electrothermal effect and the high electrical energy outputs of 520 mV. The solar evaporator has good salt tolerance and excellent cycle stability, maintaining a high evaporation rate in high‐salt solutions and after 24 cycles of testing. The outdoor evaporation tests reveal the encouraging performance of the steam and energy generators in real environment. Such superior performance of comprehensive device has great potential for integrated and sustainable application in cogeneration systems. Abstract : A solar evaporator based on carbonized sphagnum palustre is fabricated for simultaneous steam‐electricity generation enhanced by a self‐driven electric heater.